The Role of the Non-Partisan Movements in Democracy: The Portuguese Case (Global Journal of Human-Social Science, 2020)
Since its birth in Greece, democracy has evolved mainly with regard to the role people or citizens must play in the system. That evolution explains not only the various modalities of democracy but also the formation of political parties and their change over time. There is no democracy without the parties, but the parties are not the owners of the democratic system, and this encourages the appearance of non-partisan movements that wish to be part of the power play. In Portugal, during Salazar's dictatorship, political parties were forbidden. After returning to democracy, Portuguese law currently does not allow regional or local parties, as political parties need to act at the national level. However, the Constitution stipulated that non-partisan groups had the right to present lists to the lowest level of local power, the parish council. Despite the official constraint, these groups accepted the challenge, and their power and influence have increased since the first local election in 1976, and it was no wonder that, after the 1997 constitutional revision, the law had recognized them the right to apply for all the organs of the local power.
Keywords: non-partisan movements; political system; representative and deliberative democracy; and Portugal